Komunikasi Verbal dan Non Berbal dalam Pembelajaran - Parianto Parianto; Siti Marisa (Program Pascasarjana UIN Sumatera Utara, 2022)
Verbal communication is communication that uses spoken or written language as a tool to convey messages. Examples are talking, writing letters, sending text messages, and so on. Nonverbal communication is communication that does not use spoken or written language, but through signs, gestures or expressions that can be observed visually. Examples are facial expressions, body movements, or even the way someone dresses. In learning, verbal and nonverbal communication is an important part to facilitate the teaching and learning process. Teachers can use verbal communication to provide explanations or give assignments to students, while nonverbal communication can be used to show attitudes or feelings during the teaching and learning process. By using both of them effectively, teachers can create a more enjoyable learning atmosphere and help students more easily understand the material being taught